The Analysis of Causes of Inpatient Medical Records Delayed Retrieval at Muna Anggita Hospital Bojonegoro, Indonesia - Selvia Juwita Swari; Cindy Kurnia Ressa Fransiska; Demiawan Rachmatta Putro Mudiono; Erna Selviyanti; Gamasiano Alfiansyah; Maya Weka Santi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
The delayed retrieval (return) of medical records at Muna Anggita Hospital Bojonegoro in January-May 2022 hindered the data process, reporting, and BPJS claim submissions. It also impeded services when patients underwent health check-ups and affected the quality of hospitals and patient satisfaction. This study aims to analyze the factors causing the tardy return of inpatient medical records based on Lawrence Green's behavior theory, which includes predisposing, enabling, and reinforcing factors. This qualitative study collected data through interviews, observations, documentation, USG (Urgency Seriousness and Growth), and brainstorming. The research subjects include one medical record head, two assembling officers, and four inpatient ward heads. The results indicated that predisposing factors included the lack of knowledge of ward heads and their attitude (behavior) towards extending the return time of medical records. These predisposing factors can occur due to the lack of supporting facilities. Also, motivating external factors such as rewards or reprimands from ward heads and minimal socialization of standard operating procedures (SOPs) regarding borrowing and return of medical records also contribute to the delay. Behavioral factors refer to the ward heads' lack of compliance and discipline in returning medical records. Muna Anggita Hospital should conduct SOP socialization every three months and regularly provide supporting facilities. The ward heads should also set an example regarding medical record return punctuality. The subsequent researchers are encouraged to formulate a strategic plan to reduce the delays in returning inpatient medical records at Muna Anggita Hospital in Bojonegoro.